2014
DOI: 10.1080/00405000.2014.952137
|View full text |Cite
|
Sign up to set email alerts
|

An eco-friendly, permanent, and non-leaching antimicrobial coating on cotton fabrics

Abstract: A permanent, non-leaching antibacterial finish for cotton textile fabric was prepared by a sol-gel process using quaternary ammonium-modified triethoxysilane. The transparent coating was investigated against Staphylococcus aureus (Gram positive) and Escherichia coli (Gram negative) bacterial strains. A rapid decrease in bacterial count was observed within 48 h. The correlation between concentration of modified silane and antibacterial activity was studied. It was observed that this treatment had no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The results revealed improvements in fragrance durability and antimicrobial performance of cotton fabric treated with the b-Cyclodextrin/Grafted Chitosan and lavender oil. Similarly, Saif et al [183] reported an eco-friendly, permanent and non-leaching antimicrobial activity of cotton fabric coated with quaternary ammonium-modified triethoxysilane by a sol-gel process. The coating proved to provide very good wash fastness with no significant decrease in antibacterial properties even after 15 laboratory washing cycles.…”
Section: Cotton Wet Processing and Finishingmentioning
confidence: 94%
“…The results revealed improvements in fragrance durability and antimicrobial performance of cotton fabric treated with the b-Cyclodextrin/Grafted Chitosan and lavender oil. Similarly, Saif et al [183] reported an eco-friendly, permanent and non-leaching antimicrobial activity of cotton fabric coated with quaternary ammonium-modified triethoxysilane by a sol-gel process. The coating proved to provide very good wash fastness with no significant decrease in antibacterial properties even after 15 laboratory washing cycles.…”
Section: Cotton Wet Processing and Finishingmentioning
confidence: 94%
“…A transparent coating on cotton textile using quaternary ammonium-modified triethoxysilane was developed by sol–gel process, which demonstrated its permanent non-leaching antibacterial finish. The significant antimicrobial activity against S. aureus and E. coli was observed even after 15 washing cycles [ 51 ]. Some antimicrobial cotton fabrics prepared through polyhexamethylene guanidine hydrochloride and polypropylene glycol diglycidyl ether demonstrated a significant antimicrobial activity even after laundered with detergent solution [ 52 ].…”
Section: Types Of Antimicrobial Textilesmentioning
confidence: 99%
“…These inorganic NPs serve as leachable biocides that can be released from CF to kill the surrounding bacteria. However, CF coated with leachable biocides are usually lacking in durable antibacterial activity after long-term use because of the limited loading content. , Hence, long-lasting antibacterial CF may play an important role in improving antibacterial efficiency, preventing infections, and protecting human health.…”
Section: Introductionmentioning
confidence: 99%